(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Surface water contamination by heavy metals poses significant ecological and public health challenges, particularly in rapidly urbanizing regions of developing nations. This study assessed the concentration, distribution, and associated ecological and health risks of potentially toxic elements in the Ona River, located within the Adeoyo region of Ibadan, Oyo State, Nigeria. Water samples were collected from three georeferenced sites and analyzed for Fe, Zn, Cu, Cr, As, Cd, Ni, Mn, and Mg using Atomic Absorption Spectrophotometry (AAS) following APHA (2022) standard protocols. Contamination indices including the Geo-accumulation Index (Igeo), Enrichment Factor (EF), Contamination Factor (CF), Pollution Load Index (PLI), and Ecological Risk Index (ERI) were employed to evaluate pollution intensity, while non-carcinogenic and carcinogenic health risks were computed using the United States Environmental Protection Agency (USEPA) model. Results revealed that Cr, Cd, As, Pb, and Fe concentrations were within permissible limits of WHO (2022) and Nigerian Standards for Drinking Water Quality (NSDWQ, 2015). In contrast, Ni and Mn exceeded recommended thresholds, indicating localized anthropogenic inputs, primarily from industrial and urban effluents. Nickel exhibited the highest CF (2.86–3.86) and EF (1735.29–3748.24), denoting considerable contamination and extreme enrichment, while PLI values below 1 suggested overall unpolluted status. The ERI values (15.87–21.78) indicated low ecological risk; however, Ni emerged as the most significant contributor to potential toxicity. Although the Hazard Index (HI < 1) implied minimal immediate health effects, long-term exposure may pose latent risks. The study concludes that while the Ona River water remains largely unpolluted, elevated Ni and Mn levels necessitate continuous monitoring, stricter effluent regulation, and sustainable watershed management to protect aquatic ecosystems and public health.